A new species of Masdevallia (Orchidaceae Pleurothallidinae) from Perú - Valenzuela Gamarra, Luis (Lankesteriana: International Journal on Orchidology, 2008)
Masdevallia vilcabambensis, a new species from the department of Cuzco in Peru, is described and illustrated. It is similar to M. minuta, but it has much smaller plants and flowers, the flowers are yellowish and blotched with purple, and the sepals abruptly reflexed at the middle. Also, M. vilcabambensis is exclusively know from around 2500 meters elevation, whilst M. minuta is restricted to warm regions below 350 meters of altitude.